2022
DOI: 10.1093/gerona/glac152
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Levels Associated With Cognitive Functioning and Executive Function in Older Adults

Abstract: Brain deterioration with age is associated with inflammation and oxidative stress that result in structural and functional changes. Recent studies have indicated that coenzyme Q10 (CoQ10) is associated to neurological oxidative stress and cognitive impairment. Studies with older people have shown a relationship between neurodegenerative diseases and CoQ10 levels. However, no studies have analyzed the relationship between CoQ10 and cognitive functioning in older adults. The aim of this study was to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…CoQ 10 is a critical cofactor in the mitochondrial chain of electron transport and has been found to have neuroprotective, anti-inflammatory, and antioxidant effects in nervous system 64 66 . Consistently, there is clinical evidence indicating that attenuation of cognitive capacities in older adults is associated with reduced plasma concentration of CoQ 10 67 , 68 . In line with this evidence, experimental findings have revealed that systemic administration of CoQ10 (10 mg/kg) effectively reverses the impairment of spatial and avoidance memory in rodents 48 .…”
Section: Discussionmentioning
confidence: 70%
“…CoQ 10 is a critical cofactor in the mitochondrial chain of electron transport and has been found to have neuroprotective, anti-inflammatory, and antioxidant effects in nervous system 64 66 . Consistently, there is clinical evidence indicating that attenuation of cognitive capacities in older adults is associated with reduced plasma concentration of CoQ 10 67 , 68 . In line with this evidence, experimental findings have revealed that systemic administration of CoQ10 (10 mg/kg) effectively reverses the impairment of spatial and avoidance memory in rodents 48 .…”
Section: Discussionmentioning
confidence: 70%
“…In neurological contexts, CoQ10 supplementation has successfully reversed age‐related memory decline in mice by decreasing ROS and lipid peroxidation, 58 indicating potential applications in neurodegenerative diseases. Recent studies involving elderly individuals have also shown a positive correlation between plasma CoQ10 levels and cognitive and executive functions 59 . These findings underscore CoQ10's significant role in aging and its effectiveness in bolstering antioxidant defenses.…”
Section: Strategies For Maintaining Mitochondrial Redox Homeostasismentioning
confidence: 71%
“…Recent studies involving elderly individuals have also shown a positive correlation between plasma CoQ10 levels and cognitive and executive functions. 59 These findings underscore CoQ10's significant role in aging and its effectiveness in bolstering antioxidant defenses. However, further research and clinical trials are necessary to fully ascertain CoQ10's benefits, optimal dosages, and supplementation duration for effectively addressing age-related conditions linked to mitochondrial dysfunction and oxidative damage.…”
Section: Coenzyme Q10 (Coq10)mentioning
confidence: 89%